Metal type and aggregate microenvironment govern the response sequence of speciation transformation of different heavy metals to microplastics in soil - Yu, Hong; Zhang, Zheng; Zhang, Ying; Fan, Ping; Xi, Beidou; Tan, Wenbing (The Science of the total environment, 2021)
Microplastics change the physical, chemical, and biological processes in soil, and these changes further affect the transformations of heavy metal speciation in soil. Whether this influence mechanism differs between heavy metals is unknown on the soil aggregates level. In this study, 5 months incubation experiments and soil fractionation were conducted to evaluate the effect of microplastic addition on the chemical speciation of seven heavy metals (Zn, Cu, Ni, Cd, Cr, As, and Pb) in the three soil aggregate fractions. The results show that 28% concentration of polyethylene microplastics with size 100 μm reduces and increases the heavy metal content in the bioavailable and organic-bound fractions, respectively, indicating that microplastics promote the transformation from bioavailable to organic-bound species. The transformation in the larger-sized aggregate fractions is more dramatic than that of smaller-sized aggregate fractions within the incubation period. This indicates that the extent of the response of the different heavy metals to microplastics is significantly different in the three aggregate-size fractions. Soil physicochemical factors affected different heavy metals in different pathways, and microplastics have different adsorption or complexation effects on different heavy metals. These processes result in heterogeneous responses of different heavy metals to microplastic addition. In addition, the microplastics have different extents of influence on the different chemical speciation of the heavy metals, having the greatest influence on the exchangeable and carbonate-bound of Cu and Zn, FeMn oxide-bound of As, and organic-bound of Cr, Ni, Cd, and Pb. This phenomenon is relatively consistent among the three aggregate-size fractions. Our findings provide more accurate management information for soil environmental quality management with different heavy metal pollution and different soil types. [Display omitted] •Microplastics stimulated heavy metal (HM) transformation from bioavailable to organic bound.•The stimulation degree was different across HMs and soil aggregate fractions.•Microplastics affected HM speciation through direct adsorption and changing soil properties.•pH and DOC were significant factors affecting HM speciation in the presence of microplastics.